Causal Role of the Right Dorsolateral Prefrontal Cortex in Organizational Fairness Perception: Evidence From a Transcranial Direct Current Stimulation Study - Li, Xi; Xiong, Guanxing; Dong, Zhiqiang; Cai, Shenggang; Zhao, Jun; She, Zhe; Guo, Yuchen (Frontiers in Behavioral Neuroscience, 2020)
The right dorsolateral prefrontal cortex (rDLPFC) plays an essential role in social decision-making. Although several neural image studies have provided evidence that the rDLPFC is correlated with fairness perception, little research has investigated the causal effect of this encephalic region on individuals’ consciousness, particularly perceptions of organizational fairness. The present study explores the causal relationship between the rDLPFC and organizational fairness perception by using brain modulation techniques. Healthy participants received transcranial direct current stimulation and fulfilled the modified ultimatum game in the sham-controlled experiment. Our results showed that only cathodal stimulation of the rDLPFC resulted in increasing rejection offers compared with sham stimulation in conditions of disadvantageous inequity. No differences were found between anodal and sham stimulation in any inequity condition. This study strengthens the main functional effects of the rDLPFC in negative emotional control in relation to organizational fairness perceptions.